Finance : a fine art - Fleuriet, Michel (Chichester : Wiley, 2003)
Elucidates on the delicate fusion of the art and science of finance required by successful practitioners in the financial markets today.
Includes bibliographical references and index.
oif 27/08/15
Loan
Keywords: Finance; Economics; Investments